Incidence and risk factors for the development of epidermoid carcinoma in oesophageal achalasia†. (18th December 2018) - Tassi, Valentina; Lugaresi, Marialuisa; Mattioli, Benedetta; Fortunato, Francesca; Zagari, Rocco Maurizio; Daddi, Niccolò; Bassi, Francesco; Pilotti, Vladimiro; Mattioli, Sandro
Abstract: OBJECTIVES: The risk factors for oesophageal achalasia, a precancerous condition that can lead to epidermoid carcinoma, are unknown. The aim of this study was to determine these factors. METHODS: Beginning in 1973, patients presenting with achalasia from 1955 to 2016 periodically underwent clinical assessment, the barium swallow test (the oesophageal diameter and residual barium column were measured) and endoscopy according to a prospective protocol. We included patients with the minimum follow-up duration of 12 months. RESULTS: Of 681 cases, 583 patients were considered. The median follow-up time was 147.13 months (interquartile range 70.42–257.82 months), and 17 epidermoid carcinomas and 1 carcinosarcoma were diagnosed. After excluding 4 achalasia patients admitted with a cancer diagnosis, the incidence rate of epidermoid carcinomas was 1.61/1000 persons-year, and the cumulative probability of developing cancer at 56.34 years of follow-up was 13%. Risk factors for cancer were a sigmoid oesophagus [risk ratio (RR) = 17.64, 95% confidence interval (CI) 4.13–75.43], duration of achalasia symptoms >280 months (RR = 19.62, 95% CI 4.59–83.80), duration of follow-up >353 months (RR = 5.96, 95% CI 2.50–14.18), oesophageal diameter at diagnosis >71 mm (RR = 21.07, 95% CI 9.29–47.82), residual barium column at diagnosis >23 cm (RR = 24.27, 95% CI 6.93–85.01) and residual barium column at the last follow-up >10 cm (RR = 8.15, 95% CI 2.40–27.62). Conversely, the risk of epidermoid carcinoma was lower when the residual barium swallow decreased by >57% (RR = 0.10, 95% CI 0.03–0.34). CONCLUSIONS: Patients with achalasia carry a substantial risk of developing epidermoid carcinoma. Several factors, such as sigmoid achalasia and dysphagia lasting more than 23 years, are associated with an increased risk of cancer. An effective Heller myotomy may positively influence the carcinogenetic process.